Development and Cross-Validation of the Short Form of the Cultural Competence Scale for Nurses - Duckhee Chae, PhD, RN; Yunhee Park, PhD, RN (Elsevier, 2018)
Purpose: To develop and validate the short form of the Korean adaptation of the Cultural Competence Scale for Nurses. Methods: To shorten the 33-item Cultural Competence Scale for Nurses, an expert panel (N = 6) evaluated its content validity. The revised items were pilot tested using a sample of nine nurses, and clarity was assessed through cognitive interviews with respondents. The original instrument was shortened and validated through item analysis, exploratory factor analysis, convergent validity, and reliability using data from 277 hospital nurses. The 14-item final version was cross-validated through confirmatory factor analysis, convergent validity, discriminant validity, known-group comparisons, and reliability using data from 365 nurses belonging to 19 hospitals. Results: A 4-factor, 14-item model demonstrated satisfactory fit with significant factor loadings. The convergent validity between the developed tool and transcultural self-efficacy was significant (r = .55, p < .001). The convergent validity evaluated using the Average Variance Extracted and discriminant validity were acceptable. Known-group comparisons revealed significant differences in the mean scores of the groups who spent more than one month abroad (p = .002) were able to communicate in a foreign language (p < .001) and had education to care for foreign patients (p = .039). Cronbach's α was .89, and the reliability of the subscales ranged from .74 to .91. Conclusion: The Cultural Competence Scale for Nurses-Short Form demonstrated good reliability and validity. It is a short and appropriate instrument for use in clinical and research settings to assess nurses' cultural competence. Keywords: cultural competence, psychometric properties, nurse